Counterintelligence Risks in Crew Management and Recruitment: The Role of Profiling and Screening in Shipping Companies - Anastasios-Nikolaos KANELLOPOULOS (Bulletin of "Carol I" National Defense University, 2024)
This paper examines the critical role of profiling screening in countring security threats within the maritime industry, focusing on crew management and recruitment processes.In light of the industry’s susceptibility to espionage, terrorism, and sabotage, effective counterintelligence measures are imperative. By scrutinizing the vulnerabilities and best practices associated with profiling screening, shipping companies can fortify their security defenses, mitigate insider threats, and ensure the safety of their assets and personnel.